2020
DOI: 10.1002/ccd.28709
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic preconditioning reduces the incidence of contrast‐induced nephropathy in patients undergoing coronary angiography/intervention: Systematic review and meta‐analysis of randomized controlled trials

Abstract: Background: Contrast-induced nephropathy (CIN) is associated with increased mortality and morbidity in patients undergoing coronary angiography (CAG) and percutaneous coronary intervention (PCI). We aimed to assess the latest evidence on the effect of remote ischemic preconditioning (RIPC) on the incidence of CIN in patients undergoing CAG/PCI. Methods: We performed a comprehensive search on topics assessing RIPC and CIN in CAG/PCI patients from inception up until July 2019 through several electronic databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Our study has found that RIC was not only effective in reducing the incidence of CA-AKI in AMI, but also associated with an improved long-term prognosis. The current meta-analysis has extended previous finding that that RIC was effective in reducing CA-AKI in elective PCI [37,38]. In addition, our meta-analysis has indicated that RIC also showed a long-term cardiac protection in reducing MACE.…”
Section: Discussionsupporting
confidence: 76%
“…Our study has found that RIC was not only effective in reducing the incidence of CA-AKI in AMI, but also associated with an improved long-term prognosis. The current meta-analysis has extended previous finding that that RIC was effective in reducing CA-AKI in elective PCI [37,38]. In addition, our meta-analysis has indicated that RIC also showed a long-term cardiac protection in reducing MACE.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, RIC may also activate antiapoptotic (40), antioedema (41), and anti-inflammatory signalling pathways (42), improve microvascular endothelial function (43), and affect the transcription of related genes and mitochondrial respiratory function (44,45), thereby reducing the impact of I/R injury. Clinical trials on RIC renal protection have been conducted in a variety of surgical types, including cardiac surgery, macrovascular surgery, and percutaneous coronary intervention, and this approach has gradually become a promising renal protection strategy and has been demonstrated in experimental and clinical studies (46)(47)(48). At present, a large number of meta-analyses have shown the protective effect of RIC on the kidney, such as renal protection after coronary angiography or interventional patients with contrast agents (46).…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvement in medullary and cortex oxygenation following the RIPC procedure has been shown in humans [ 35 ]. Previous large randomised trials of the effect of RIPC on renal biomarkers and kidney function have led to promising results [ 36 ]. However, often conflicting results have been found due to heterogeneity of study designs and populations.…”
Section: Discussionmentioning
confidence: 99%